An improved polymer solar cell incorporating single-wall carbon nanotubes - Lu, Fen (2015)
We present an improved efficiency of polymer solar cell by incorporating single-wall carbon nanotubes (SWCNTs). A power conversion efficiency of 2.66% was achieved for the device with 0.125 wt% SWCNTs, which is 16% improvement over control device without SWCNTs, primarily due to the increase in the photocurrent and fill factor. The results reveal that SWCNTs serve as effective and additional electron pathways, facilitating the electron transport and improving the interface contact between active layer and electrode. The improved contact area was evidenced by the increased root-mean-square surface roughness as SWCNTs concentration increases. However, the increased peak-to-valley value also indicates the possibility of short circuit in device, thus the concentration of SWCNTs has to be optimized.